تحليل احصائي للبيانات متعددة الحدود باستخدام النموذج الخطي المعمم ( دراسة ميدانية على الكافيتريات في محافظة السليمانية) م - سعيد, خالدة علي (Sulaimani Journal for Humanities, 2021)
In this research introduces the use of the descriptive analytical approach using several statistical methods appropriate for the Multinomial data (nominal and ordinal) where collected by Survey study from cafeterias in the Sulaimani governorate and in various social environments and hesitants of both gender to identify the positive and negative effects created by a cafeteria on the environment socially, economically, and healthily, determining the causal importance and studying the relationship between the factors and reasons for visit, hours of stay in a cafeteria, and the daily expenses cost for each visit, through the use of the Generalized Linear Model (GLM). It was connected that the frequent visitors who visit a cafeteria with friends are of both gender and in age categories15-24 years and 25- 34 years. They have a secondary certificate & less, and are not married and they are either workers or unemployed and remain in the cafeteria from 3 to 6 hours and that to wasting time, and distract between (5000 - 9000) ID per visit. Also, the majority of workers in this field are both genders and their ages between 20-29& 30-39 and unmarried, they have a secondary certificate & less. About the generalized linear models used it is suitable for testing the three response variables (reasons for visit, hours of stay in a cafeteria, and the daily expenses cost for each visit) with high efficiency. And we concluded that the main reason behind the increase in the number of cafeterias in general and in the Sulaimani governorate in particular lies behind widespread unemployment among young people, and the abundance of leisure time, in addition the cafeteria projects it is successful projects and achieving a lot of profit in a short period for their owners. And we recommendation to the relevant stakeholders with more attention to youth and solve the problem of unemployment and provide job opportunities for young people to benefit from their energy in jobs and fields that benefit society. Monitor the healthy environment of cafeterias and reduce congestion in them, and her concern for the cleanliness of the place is located there in order not to be a focus for infectious diseases, inconvenience and deviation young people.